ANALISIS HUKUM ISLÂM TERHADAP MASALAH KEKERASAN DALAM RUMAH TANGGA (KDRT) - Abd. Wahed (Al-Ihkam: Jurnal Hukum dan Pranata Sosial)
KDRT (domestic violence) must be ended. Both wife and husband come to a conclusion to finish it. However, it doesn't mean that the role of a husband, as discipline upholder, has to be denied. Islam does not agree with it. As an Imam (leader), a husband must maintain moral values to establish a peaceful and perfect harmonious family. UU. No 23 Th. 2004 implicitly states that domestic violence is any violence types occurring in a family. A husband has been a person who always be blamed on in this case. This article analyzes a kind of violence committed by a husband against the family members--- children and wife from the perspective of Fiqh (Islamic law)